Natural Ventilation in a Semi-Confined Enclosure Heated by a Linear Heat Source - Koueni, Toko Christian Anicet (Transactions on Engineering and Computing Sciences, 2024)
This work aims to study by numerical computation the natural ventilation in an enclosure with six openings heated by a solid and linear heat source. The study is carried out in steady state for the values of the reduced Rayleigh number Ra* = 6.09 × 107, 9.74 × 107 and 1.61 × 108. The numerical computation device has an aspect ratio H/L = 2.46. The heat source is centered and located near the floor of the enclosure. The openings are symmetrical in pairs and located on the two side walls located at positions x+ = - 0.5 and 0.5. The numerical studies were carried out by DNS considering that the heat source is initially at constant temperature. The finite volume method was used to discretize the conservation equations of mass, momentum and energy of the problem studied. The results show the existence of the thermal plume deviated towards x+ > 0. The fields and temperature profiles and static pressure profiles are non-homogeneous in the enclosure. A asymmetrical phenomenon is observed in the stationary enclosure of the differential static pressure profiles and a heating. The differential static pressure profile located at position x = - 0.5 is different from that at position x+ = 0.5. Fresh air enters the enclosure through openings located below the height z+ = 0.65. The fresh air which enters the enclosure through the opening located at position z+ = 0.59 mixes with the hot gas from the thermal plume and lowers its temperature for Rayleigh numbers of 6.09 × 107, 9.74 × 107 and 1.61 × 108 . The hot gases exit the enclosure through openings located in the ceiling of the enclosure. The results of numerical computation of differential static pressure obtained near the position x+ = 0 agree with those of experimental measurements in the literature.